Identitas Sosial Gereja - Arly de Haan; Anika Chatarina Takene; Darniyati Amtiran (Institut Agama Kristen negeri Kupang, 2021)
This article discusses the social identity of the early church according to the book of Acts. Social identity is understood as a value that is built together in a group and this value becomes the identity of the group. In obtaining the results of the study, we used the literature study method to examine the literature including examining key words in Greek. There are six keywords, namely pisteuontes, homothumadon, sunegmenoi, diakonein, douleon, and huperetein. These six words describe the values ??that became the identity of the early church, namely living in fellowship and service. The Holy Spirit makes the church community is a community of of fellowship. This term describes the ritual aspect that is carried out continuously to maintain a solid community, which is based on God's love. Another aspect that is strengthened is the aspect of loving service, which is part of the actual life of the community. Serving of love is done holistically, not only exclusively for the fellowship community but also for the society. This ministry is a distinguishing feature for the church community, as well as the most effective means of evangelism. Keywords: fellowship, church, identity, Acts